Model Problem Based Learning dengan Pendekatan Scientific Efeknya pada Output Pembelajaran Siswa Kelas X MIPA 6 Mata Pelajaran PAI di SMA Negeri 1 Majenang Kabupaten Cilacap - Kartika Wanojaleni; Arum Septia Dyah Ayu Nurfajri (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to determine the problem based learning model with a scientific approach its effect on the learning output of class X MIPA 6 PAI subjects at SMA Negeri Majenang, Cilacap Regency. This Research Type Field Research (Field Research) Using a qualitative approach. Methods of data collection in the form of observation, interviews and documentation. The results showed that scientific learning using a problem based learning model, namely: 1) observing, the teacher displays pictures of how to dress men and women and all students observe pictures of how to dress men and women; 2) asking questions, teachers and students actively ask questions about the results of student observations regarding the images provided; 3) explore, students look for answers to questions on the initial ability check and collect information from questions and answers, the teacher asks each group to take a number at random and look for material according to the number obtained and each group look for material according to the division; 4) associate, students compile the results of the discussion; 5) communicating, the teacher invites each group representative to present the results of the discussion, other students are welcome to give responses to the answers given by their friends and the teacher evaluates using the talking stick method and carefully. After learning, evaluation is carried out in the attitude domain in the form of observation, in the cognitive domain in the form of talking sticks and in the psychomotor domain in the form of performance or presentation. The learning output produced by students is more critical, the average quantitative value is 9, and students are more creative.